Bacterial intestinal microflora and diseases of the liver - Ye. A. Fedosyina; M. S. Zharkova; M. V. Maevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To analyze the literature data on application of prebiotics in treatment of metabolic disorders at diseases of the liver.Original positions. As it is known, diverse functions of gastro-intestinal tract are related to vital activity of intestinal microflora. The normal microflora sustains colonization resistance of the body, prevents development of pathogenic and opportunistic flora. In the case of disorders of this major function the number of potentially pathogenic microorganism is increased and the spectrum extends, their translocation through intestinal wall may occur that can be accompanied by development of endogenous infection or superinfection. Recently the role of bacterial overgrowth in pathogenesis of non-alcoholic steatohepatitis is widely discussed. At obesity entry of free fatty acids in the liver is increased and steatosis of the liver develops that is considered to be «the first blow». The oxydative stress («the second blow») which takes place at bacterial overgrowth syndrome as well due to increased endogenous secretion of ethanol and lipopolysaccharides, stimulating excessive production of proinflammatory cytokines by Kupffer’s cells, educes consequtively or simultaneously. Bacterial overgrowth syndrome along with immunodepression, change of permeability of intestinal wall also participates in pathogenesis of bacterial translocation, and then — in development of infections at liver cirrhosis (LC).Conclusion. Scientific studies showed efficacy of prebiotics (alimentary fibers) as the drugs providing normal activity of intestinal microflora that promotes prophylaxis and treatment of liver diseases, including at patients with the LC, bacterial overgrowth, minimal hepatic encephalopathy, non-alcoholic steatohepatitis.